Ultrasound in Trauma and Other Acute Conditions in Sports, Part I. Issue 11 (November 2020) - Hahn, Marlee; Ray, Jeremiah; Hall, Mederic M.; Coe, Ian; Situ-LaCasse, Elaine; Waterbrook, Anna L.
Abstract : Abstract: The utility of ultrasound in sports medicine is improving the sports medicine physician's ability to rapidly diagnose and treat a multitude of sports related pathologies. In this article, we clearly outline the current status of the evidence in support of using sports ultrasound in the setting of acute abdominal and thoracic trauma, acute lung illness, limited cardiac evaluation of a collapsed athlete, volume status assessment, and fracture evaluation. Abstract : Supplemental digital content is available in the text.